Arctic ozone loss in threshold conditions: Match observations in 1997/1998 and 1998/1999 - Schulz, A.; Rex, M.; Harris, N.; Braathen, G.; Reimer, E.; Alfier, R.; Kilbane-Dawe, I.; Eckermann, S.; Allaart, M.; Alpers, M.; Bojkov, B.; Cisneros, J.; et al. (Journal of Geophysical Research: Atmospheres, 2001)
International audience Chemical ozone loss rates inside the Arctic polar vortex were determined in early 1998 and early 1999 by using the Match technique based on coordinated ozonesonde measurements. These two winters provide the only opportunities in recent years to investigate chemical ozone loss in a warm Arctic vortex under threshold conditions, i.e., where the preconditions for chlorine activation, and hence ozone destruction, only occurred occasionally. In 1998, results were obtained in January and February between 410 and 520 K. The overall ozone loss was observed to be largely insignificant, with the exception of late February, when those air parcels exposed to temperatures below 195 K were affected by chemical ozone loss. In 1999, results are confined to the 475 K isentropic level, where no significant ozone loss was observed. Average temperatures were some 8°-10° higher than those in 1995, 1996, and 1997, when substantial chemical ozone loss occurred. The results underline the strong dependence of the chemical ozone loss on the stratospheric temperatures. This study shows that enhanced chlorine alone does not provide a sufficient condition for ozone loss. The evolution of stratospheric temperatures over the next decade will be the determining factor for the amount of wintertime chemical ozone loss in the Arctic stratosphere.